Dampak Model Pembelajaran Reciprocal Teaching terhadap Kemampuan Berpikir Kritis Siswa SMA - Khoirunnisa Lili Rahmawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effect of the reciprocal teaching learning model on the critical thinking skills of SMAN 4 Madiun students. The method used is Pretest-Posttest Control Group Design. The results showed that the tcount obtained was 133,955 (> ttable 2,080). In conclusion, there is an effect of applying the reciprocal teaching learning model to the critical thinking skills of SMAN 4 Madiun students. Keywords: Critical Thinking, Learning Model, Reciprocal Teaching